2017
DOI: 10.2147/cia.s140309
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits and self-care behaviors in elderly adults with heart failure

Abstract: IntroductionElderly adults with heart failure (HF) may have problems with self-care behaviors because of cognitive deficits. Self-care deficits have been found to be significantly associated with negative health care outcomes among HF patients. The aim of this paper was to assess cognitive deficits and the level of self-care ability in elderly patients with HF, and to determine if a relationship exists between cognitive deficits and self-care.Materials and methodsThe study included 270 elderly patients (mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
47
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 43 publications
9
47
1
5
Order By: Relevance
“…Cognitive abilities are required to maintain a certain level of knowledge and perform self-care. The elderly can have problems with hearing, vision and cognitive deficits, these factors can all influence the outcome of patient education and become a barrier to attending CR [27]. The elderly represent a large part of the overall HF population, and many of them are widowed and living alone.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive abilities are required to maintain a certain level of knowledge and perform self-care. The elderly can have problems with hearing, vision and cognitive deficits, these factors can all influence the outcome of patient education and become a barrier to attending CR [27]. The elderly represent a large part of the overall HF population, and many of them are widowed and living alone.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with HF are less likely to adhere to self‐care behaviours than younger patients are (Cocchieri et al., 2015). Hence, studies to discover meaningful factors influencing self‐care in patients with HF have continued and in recent years, significant factors have been reported, including age, education, New York Heart Association (NYHA) functional class, comorbidity, disease knowledge, health literacy and social support (Beckie et al, 2017; Prochota, Szwamel, & Uchmanowicz, 2019; Seid, Abdela, & Zeleke, 2019; Uchmanowicz et al., 2017). However, the implementation of self‐care for older patients with HF, in particular, is still an issue that needs attention (Prochota et al., 2019; Uchmanowicz et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Walker et al [31] found that social determinants of health were significantly associated with diabetic knowledge, self-care, and outcomes. Uchmanowicz et al [32] suggested that higher education was associated with higher cognitive function and better self-care.…”
Section: Discussionmentioning
confidence: 99%